Business Sustainability through Halal Supply Chain, Green Finance, and Digital Literacy: Second-Order SEM Approach - Aidha, Nurul; Sari, Ria Nelly; Basri, Yesi Mutia (Pusat P2M Politeknik Negeri Batam, 2025)
Business sustainability is crucial for every business. Understanding the factors that drive and sustain sustainability helps business actors develop effective strategies. This study examines the effects of Halal Supply Chain, Green Finance, and Digital Literacy on Business Sustainability. The population was culinary sector SMEs in Pekanbaru City that had halal certification and at least 2 years of operation. Slovin's formula determined the sample size. Data were collected via questionnaires, yielding 170 valid responses. The analysis used the Second-Order SEM approach. Results show that Halal Supply Chain and Digital Literacy positively affect sustainability in culinary SMEs, while Green Finance does not. Integrating Halal Supply Chain and Digital Literacy practices helps culinary SMEs sustain their business.